Comparative evaluation of growth, yield and yield attributing traits in sugarcane (Saccharum officinarum) under different soil moisture regimes - DHANSU, POOJA; NANDWAL, A S; KUMAR, SURENDER; CHAND, MEHAR; RANI, BABITA; KULSHRESHTHA, NEERAJ (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during spring season of 2014–15 and 2015–16 at CCS HAU, RRS, Karnal to evaluate the response of four sugarcane (Saccharum officinarum L.) varieties differing in their maturity i.e. CoS 767 (Mid late), CoH128 (Mid late), CoJ 64 (Early) and Co 0238 (Early) to deficit irrigation. The experiment was conducted in split plot design with three replications. Based on available soil moisture (ASM), three treatments i.e. irrigation at 50% ASM (control), 40% ASM (mild stress) and 30% ASM (severe stress) were imposed in main plot and sugarcane varieties in sub-plot. Under deficit irrigation, leaf area, leaf area index (LAI), crop grown rate (CGR), relative growth rate (RGR) and net assimilation rate (NAR), significantly, reduced at 30–60 and 60–90 DAP in all the varieties and the varieties Co 0238 and CoS 767 showed least reduction. The yield parameters, viz. number of millable canes, cane length, internodal length and single cane weight reduced significantly under water limited conditions and proved to be the most sensitive yield components responsible for decrease in cane and sugar yield. Cane yield and sugar yield reduced by 36.18% and 40.47%, and 27.5% and 31.09% at 30% and 40% ASM level, respectively. Co 0238 produced highest average cane yield and sugar yield (83.05 and 10.17 t/ha) followed by CoS 767 (68.23 and 8.28 t/ ha). Moreover, after stress revival Co 0238 and CoS 767 were able to recover faster which qualified these varieties to face short periods of drought without major losses in the initial phase of development.